Social entrepreneurship in Trujillo, Peru: The case of Nisolo. Issue 3 (27th May 2018) - Holland, Joseph H.; Hatcher, William; Poole, V. Brooks
Abstract: This exploratory research examines Nisolo, a social entrepreneurship enterprise based in Trujillo, Peru, where currently its production facility seeks to hire local workers and build the surrounding community. Nisolo produces high-end shoes and tries to distribute its profits to the community of Trujillo. Using a case-study approach, our research intent is to develop a better understanding of this social entrepreneurship enterprise regarding social impact. The research uses a variety of data collection tools, including participatory observation, interviews, and a systematic review of sources consisting of private emails, photographs, videos, and newspaper articles. The findings indicate that Nisolo's social impact mission positively impacts nearly 400 individuals in the local community. By providing consistent employment, fair wages, health care, livelihood training, and a savings and salary advance program, Nisolo is not only focusing on driving social change, but on creating a sustainable model that highlights potential fashion industry changes.